The Influence of Brand Image and Perceived Value on Purchasing Decisions with Brand Trust as Mediation - Reynaldi, Reynaldi; Nuvriasari, Audita (Research Horizon, 2024)
This study investigates the impact of brand image and perceived value on purchasing decisions for H&M fashion products, with brand trust serving as a mediating factor. The sample consists of 100 respondents, and data were collected using a survey method with questionnaires as the research instrument. Data analysis was performed using the outer model, inner model, and hypothesis testing in the SmartPLS 3.2 program. The research results show that brand image has a positive and significant effect on purchasing decisions. Perceived value has a positive and significant effect on purchasing decisions. Brand trust has a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on brand trust. Perceived value has a positive and significant effect on brand trust. Brand trust significantly mediates the relationship between brand image and purchasing decisions. Brand trust significantly mediates the relationship between perceived value and purchasing decisions. These results highlight the important role of brand trust in enhancing the influence of brand image and perceived value on consumer purchasing decisions.